Coverage and determinants of childhood immunization in Nigeria: A systematic review and meta-analysis - Adeloye, Davies; Jacobs, Wura; Amuta, Ann O.; Ogundipe, Oluwatomisin; Mosaku, Oluwaseun; Gadanya, Muktar A.; Oni, Gbolahan (Vaccine, 2017)
•There are concerns over current immunization data in Nigeria.•Immunization coverage rates were estimated based on publicly available evidence.•The estimated proportion of fully immunized children in Nigeria was 34%.•Mother’s social engagements, vaccines unavailability, and safety concerns were main determinants of immunization uptake; and•There are uncertainties on the quality of evidence available, especially from the Northern states. The proportion of fully immunized children in Nigeria is reportedly low. There are concerns over national immunization data quality, with this possibly limiting country-wide response. We reviewed publicly available evidence on routine immunization across Nigeria to estimate national and zonal coverage of childhood immunization and associated determinants. A systematic search of Medline, EMBASE, Global Health and African Journals Online (AJOL) was conducted. We included population-based studies on childhood immunization in Nigeria. A random effects meta-analysis was conducted on extracted crude rates to arrive at national and zonal pooled estimates for the country. Our search returned 646 hits. 21 studies covering 25 sites and 26,960 children were selected. The estimated proportion of fully immunized children in Nigeria was 34.4% (95% confidence interval [CI]: 27.0–41.9), with South-south zone having the highest at 51.5% (95% CI: 20.5–82.6), and North-west the lowest at 9.5% (95% CI: 4.6–14.4). Mother’s social engagements (OR=4.0, 95% CI: 1.9–8.1) and vaccines unavailability (OR=3.9, 95% CI: 1.2–12.3) were mostly reported for low coverage. Other leading determinants were vaccine safety concerns (OR=3.0, 95% CI: 0.9–9.4), mother’s low education (OR=2.5, 95% CI: 1.8–3.6) and poor information (OR=2.0, 95% CI: 0.8–4.7). Our study suggests a low coverage of childhood immunization in Nigeria. Due to the paucity of data in the Northern states, we are still uncertain of the quality of evidence presented. It is hoped that this study will prompt the needed research, public health and policy changes toward increased evenly-spread coverage of childhood immunization in the country.